Produção e composição do leite de vacas mantidas em pastagens de capim-elefante submetidas a duas frequências de pastejo - Voltolini, Tadeu Vinhas; Portela Santos, Flavio Augusto; Martinez, Junio Cesar [UNESP]; Imaizumi, Hugo; Clarindo, Rafael Luis; Penati, Marco Antonio (Revista Brasileira Zootecnia Brazilian Journal Animal Sci, 2010)
The objective of this study was to evaluate two grazing intervals (IG) for elephant grass (Pennisetum purpureum Schum cv. Cameroon) pasture: one variable, determined by the entry of animals to the paddocks when 95% of active photosynthetic radiation was intercepted by the sward, and fixed 26-day grazing interval. Eight dairy cows were used, averaging 124 days lactation, 516 kg body weight and 17.5 kg daily milk production at the beginning of the trial. The experimental period was 80 days divided into four sub-periods of 20 days each. Data were analyzed in a cross-over design. The grazing frequencies did not influence milk production and composition, plasma urea nitrogen, body condition score and variations in body weight. However, the stocking rate and milk production per hectare were higher for pasture with interval of grazing determined by 95% of active photosynthetic radiation. Thus grazing frequency defined in variable intervals by sward interception of active photosynthetic radiation result in higher milk production per area unit.

Objetivou-se avaliar duas frequências de pastejo em pastagens de capim-elefante (Pennisetum purpureum Schum. cv. Cameroon): uma variável, determinada pela entrada dos animais na área a ser pastejada, quando o dossel atingisse 95% de interceptação da radiação fotossinteticamente ativa; e uma frequência fixa, de 26 dias. Utilizaram-se oito vacas com média de 124 dias em lactação, 516 kg de peso corporal e 17,5 kg de leite no início do experimento. O período experimental foi de 80 dias, divididos em quatro subperíodos de 20 dias. O delineamento experimental utilizado foi o cross-over. As frequências de pastejo não influenciaram a produção e composição do leite, o nitrogênio ureico no plasma, o escore de condição corporal e a variação de peso corporal. Entretanto, a taxa de lotação e a produção de leite por unidade de área foram maiores nas pastagens com intervalo de pastejo determinado pela interceptação de 95% da radiação fotossinteticamente ativa. Assim, a frequência de pastejo definida em intervalos variáveis por meio da interceptação da radiação fotossinteticamente ativa resulta em maior produção de leite por unidade de área.
Milk production and composition of dairy cows grazing elephant grass under two grazing intervals
Keywords: forage; dairy cows; grassland; milk production; pasture management; Pennisetum purpureum